The International Protection Alternative in Refugee Law : Treaty Basis and Scope of Application under the 1951 Convention Relating to the Status of Refugees and Its 1967 Protocol. - Schultz, Jessica (International Refugee Law Ser., 2018)
Under what circumstances can a state refuse refugee status to a person whose risk of persecution exists in only part of her country of origin? This book is the first monograph to examine the treaty basis and criteria for the 'internal protection alternative' (IPA), an exception to refugee status increasingly invoked by state parties to the 1951 Refugee Convention and its 1967 Protocol. Through a critical analysis of the relationship between refugee law and related fields, Schultz finds that the legal scope for IPA practice is narrower than is commonly claimed. Since persons subject to an IPA analysis have a well-founded fear of persecution within their countries of origin, any limit on their right to refugee status must involve a careful balancing of the impact of continued displacement against the state's interest in preserving its restricted protection resources. She argues that the doctrine of implied limits in human rights law can provide analytic structure to the IPA concept and reduce the risk of overly broad application.